Przeżywanie żałoby przez dzieci = Experiencing grief by children - Korlak-Łukasiewicz, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article deals with experiencing grief by children - a rarely undertaken topic in our culture. Children and death are the notions which seem to be very distant. One stands for the beginning and the other - the end. However, one cannot prevent a child from a loss situation. Children experience grief more often that we would expect.
Keywords: żałoba; dziecko; strata